2018
DOI: 10.17138/tgft(5)26-33
|View full text |Cite
|
Sign up to set email alerts
|

Germination of tropical forage seeds stored for six years in ambient and controlled temperature and humidity conditions in Thailand

Abstract: Germinación de semilla de forrajeras tropicales durante seis años de almacenamiento bajo condiciones ambientales y condiciones de temperatura y humedad controladas en Tailandia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
(6 reference statements)
0
5
1
Order By: Relevance
“…A study in India with four Urochloa species reported germination rates from 0.0% to 18.0% 32 . The lowest seed germination rate observed in the laboratory conditions in our study could be attributed to the germination test conditions i.e., constant temperature of 28 °C and continuous dark while other authors have reported the use of alternating day/night temperature and light in assessing seed germination of Brachiaria grass seeds 32 , 41 , 42 . We therefore, acknowledge some methodological deficiencies in the lab testing which was solely because of unavailability of incubator with provision of alternate light and temperature cycles.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…A study in India with four Urochloa species reported germination rates from 0.0% to 18.0% 32 . The lowest seed germination rate observed in the laboratory conditions in our study could be attributed to the germination test conditions i.e., constant temperature of 28 °C and continuous dark while other authors have reported the use of alternating day/night temperature and light in assessing seed germination of Brachiaria grass seeds 32 , 41 , 42 . We therefore, acknowledge some methodological deficiencies in the lab testing which was solely because of unavailability of incubator with provision of alternate light and temperature cycles.…”
Section: Discussioncontrasting
confidence: 66%
“…Use of about one year old seeds stored in ambient condition might have significantly contributed to a low germination. The practices including seed scarification, seed stratification, exposure of seeds to light, exogenous application of chemical stimulants, invigoration treatments, seed storage in a cool room and use of dry chain technologies including hermetic bags can be helpful to improve seed germination in Urochloa grass 37 , 41 , 46 – 49 . Several technologies are available to improve seed germination and other seed quality parameters but their use in many countries in Africa including in Cameroon particularly for tropical forage seed are rare/nonexistence due to limited awareness, low technical know-how, limited access to agricultural inputs and credits, low priority given to forage research and development activities, and subsistence nature of forage and forage seed production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urochloa seed deterioration over time is a universal phenomenon under unsuitable storage conditions. Most tropical species lose their seed viability very fast when stored for long under ambient conditions (Hare, 2014; Hare et al, 2018). This could have been the case for cv.…”
Section: Discussionmentioning
confidence: 99%
“…However, seeds harvested by hand‐knocking present about 30% level of immaturity and low quality. If these seeds could be harvested by ground sweeping and stored in cool environment, it could be a better option to improve germination rates because studies have revealed faster seed deterioration rates over time for some cultivars (Mulato II) under hand‐knocking and storage at ambient conditions (Hare, 2014; Hare et al, 2018). Seeds harvested in December revealed better germination rates than November.…”
Section: Discussionmentioning
confidence: 99%